1991
DOI: 10.1159/000461262
|View full text |Cite
|
Sign up to set email alerts
|

Identification by Immunoblotting of the Erythrocyte Membrane Sialoglycoproteins That Carry the Vw and Mur Antigens

Abstract: Immunoblotting of the separated membrane components of MiI erythrocytes with anti-Vw identified a band of M(r) 40,000 with a mobility close to that of β-sialoglycoprotein corresponding to the abnormal α-sialoglycoprotein present in Mil cells. A comparison of results obtained when MiIII erythrocytes were immunoblotted with anti-Mur, anti-s and the monoclonal antibody R1.3, indicated that the Mur antigen is located on the abnormal δ-sialoglycoprotein of Mr 36,000 in MiIII erythrocytes. Prior treatment of MiI ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…31-49 of the Mi.111 and Mi.VI variants was found to inhibit 'anti-Vw+Hut+Mur'. Recently, other authors [22] have reported that 'anti-Mur' binds to Mi .HI-GPB-A-B. However, the author concludes that other related antibody specificities (anti-Mia, anti-Vw plus anti-Hut+Mur) have not been excluded.…”
Section: I L L Mi Iv and Mi Vimentioning
confidence: 98%
See 1 more Smart Citation
“…31-49 of the Mi.111 and Mi.VI variants was found to inhibit 'anti-Vw+Hut+Mur'. Recently, other authors [22] have reported that 'anti-Mur' binds to Mi .HI-GPB-A-B. However, the author concludes that other related antibody specificities (anti-Mia, anti-Vw plus anti-Hut+Mur) have not been excluded.…”
Section: I L L Mi Iv and Mi Vimentioning
confidence: 98%
“…Inhibition experiments demonstrated that the Mi' and Vw antigens are located in the region of G P A exhibiting the Mi.1-or Mi.11-specific alterations [21]. Recently, the location of the Vw antigen on Mi.1-GPA has been confirmed by immunoblotting [22]. A recent abstract describes the first Mi.…”
Section: I and Mi Iimentioning
confidence: 99%